Answer:
<BAE is congruent to <DAC (first choice)
Step-by-step explanation:
Triangle ACD has three angles: <DAC, <ACD, <ADC
Triangle ABE has three angles: <BAE, <AEB, <ABE
Angles ACD, ADC, AEB and ABE are all different angles. Look them up in the figure, and you'll see they are 4 different angles.
Angles BAE and DAC are the same angle.
Answer: <BAE is congruent to <DAC (first choice)
Answer:
Step-by-step explanation:
Setting up a diagram would be helpful here, so we should have the vertical leg representing the 84-ft. tree and the horizontal leg representing the 120 ft. shadow. With the two measurements we are given, we should use the tangent ratio, opp/adj, to set up an equation to solve for the angle of elevation. So the equation will be:
tan θ = 84/120. Using the tan inverse function on the calculator, we have tan-1( 84/120) = θ and, rounding our decimal value to the nearest 10th, we have θ =35°.
The angle of elevation of the sun, formed by a 94-ft tree and its 110-ft shadow, can be found using tangent in trigonometry. The formula tan(θ) = opposite/adjacent is used, where the opposite is the height of the tree (94 ft) and the adjacent is the length of the shadow (110 ft).
In the given problem, the tree and its shadow form a right triangle with the sun forming the angle of elevation. The length of the tree represents the opposite side of the triangle, and the shadow length represents the adjacent side. To find the angle of the sun's elevation, we can use the tangent function in trigonometry, which is the ratio of the opposite side to the adjacent side.
Step 1: Define variables
Let θ be the angle of elevation.
Opposite side (o) = 94 ft.
Adjacent side (a) = 110 ft.
Step 2: Use the tangent function
The formula is tan(θ) = o/a.
Step 3: Substitute the values
We substitute our variables into the formula to get θ = tan-1(94/110).
Step 4: Calculations
You can calculate this using a scientific calculator to find the angle of elevation.
#SPJ3
Answer:
Answer is (b) The worker with 40 hours of training is paid $1400 per month
Answer:
b) b√a
Step-by-step explanation:
Given equation,
→ ab²
Then the square root of ab² is,
→ square root of ab²
→ √(ab²)
→ b√a
Hence, option (b) is the answer.
Answer:
B) b√a
Step-by-step explanation:
b√a
Your equation should look like (x + c)2 = d or (x - c)2 = d.
I
+
utan
pls help
The equation with completing the squares is (x + 8)² = 77.
An equation is a mathematical statement that is made up of two expressions connected by an equal sign.
Example:
2x + 4 = 9 is an equation.
We have,
x² + 16x - 2 = 11
We can make completesquares.
x² + 16x - 2 - 11 = 0
x² + 16x - 13 = 0
x² + 2 x 8 x (x) -8² + 8² - 13 = 0
(x² + 16x + 8²) - 64 - 13 = 0
(x + 8)² - 77 = 0
(x + 8)² = 77
Thus,
The equation is (x + 8)² = 77.
Learn more about equations here:
#SPJ2
Answer:
(x+8)^2=77 and x=negative 8±√77
Step-by-step explanation:
After watching a video, I got it right on Khan
Part C: Factor x2 − 4. Show your work
Answer:
A.2b2(x2-x-3)
B.x2+2x+2x+4
=x(x+2)+2(x+2)
=(x+2)(x+2)
C.x2-2^2
=(x+2)(x+2)
Tips:
There are 60 minutes in one hour. There
Are 24 hours in a day
Answer:
93,600 times
Step-by-step explanation: